К вопросу о земледелии племен салтовской культуры (по материалам поселения Рогалик) - Пашкевич, Г. А.; Горбаненко, С. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryG. Pasbkevich, S. Gorhanenko. Anent Agriculture of the Saltovskaya Culture Tribes (on the materials of the settlement of Rogalik)Despite records of findings of cultivated plants in materials of settlements of Saltovskaya culture in scientific literature, to this day they were not investigated credibly. In this connection a unique finding of carbonized grains, total weight about 30 kg, in the settlement of Rogalik, Lugansk district (archeological excavation made by K.I.Krasilnikov) is of great importance. Grains of bottle-shaped tunicated barley Hordeum vulgare var. lagunculiforme and cultivated oat Avena sativa prevail in the findings. It is possible that millet Panicum miliaceum has been the third important white straw crop: The findings in Rogalik expand the list of places where grains of bottle-shaped barley were found. It is obvious that these were needs of animal husbandry that forced the inhabitants of Rogalik to take up agriculture.